Determinants of Exclusive Breastfeeding Practices Among Mothers of Infants [0-6 Months] Attending Immunization Clinic in University of Port Harcourt Teaching Hospital, Rivers State - Chinyere, Dim Lilian; Kenneth, Imarenezor Edobor Peter (Darul Yasin Al Sys, 2025)
Exclusive breastfeeding (EBF) for the first six months of life is essential for an infant's optimal growth, immunity, and development. However, global adherence remains inadequate, particularly in developing regions. This study aimed to explore the factors influencing EBF practices among mothers of infants aged 0-6 months attending the immunization clinic at the University of Port Harcourt Teaching Hospital (UPTH) in Rivers State, Nigeria. A cross-sectional approach, data were gathered from 382 mothers through structured questionnaires. Analysis was done using Pearson correlation and chi-square tests. The findings showed that social support from healthcare providers, family and breastfeeding support groups played a crucial role in encouraging EBF. A substantial portion of mothers (47.1%) receive help with breastfeeding decisions from healthcare providers, followed by 39.3% from husbands or relatives and 13.6% from friends. Encouragement from husbands or family members plays a crucial role, with 83.8% of mothers reporting support in this regard. Additionally, 26.2% of mothers participate in breastfeeding support groups, and 75.9% of healthcare providers discuss the benefits of breastfeeding with them, further supporting their decisions. A notable 68.1% of healthcare providers assist with the initiation of breastfeeding, and 39.3% receive post-discharge breastfeeding support. The influence of healthcare providers in the decision to exclusive breastfeeding is significant, with 47.1% attributing their decision to this guidance. The findings show that significant correlations were observed between breastfeeding education and antenatal clinic attendance (r = 0.33, p < 0.001), as well as between belief in breastfeeding benefits and the number of antenatal visits (r = 0.22, sp < 0.01). The findings show that attending antenatal clinics, receiving breastfeeding education, and strong belief in the benefits of breastfeeding were positively associated with the practice of EBF. Additionally, factors like the place of delivery, mode of delivery, and home delivery supervisor also played a significant role in determining exclusive breastfeeding practices. Logistic regression analysis further highlighted that maternal education, healthcare support, and socioeconomic factors were key predictors of EBF practices. Conclusively, this study highlights the importance of social support, breastfeeding education, and healthcare provider encouragement in promoting EBF practices. Targeted interventions that focus on enhancing breastfeeding education during antenatal visits and addressing cultural and healthcare-related barriers are recommended to improve EBF rates among mothers attending UPTH and in Rivers State.